2022
DOI: 10.1007/s11695-022-06040-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Diabetes Improvement After Duodenal Exclusion in Zucker Diabetic Fatty Rats Is Associated with Prevention of Strain-Specific Pancreatic Remodeling and Increased Beta Cell Proliferation

Abstract: Background Response to metabolic surgery is heterogeneous and the metabolic states that underpin weight loss and metabolic improvement are still unclear. In this study, we investigate parameters of post-bariatric fasting glucoregulation and leverage artificial intelligence-assisted whole-slide image analyses to characterize associated immunohistologic features of the pancreas. Materials and Methods We performed either loop duodeno-jejunostomy (DJOS) with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…PCNA is a protein required for DNA synthesis and served as a marker of cell replication (Seifert et al. 2022 ). As showed in Figure 2a–d , I/R injury could reduce the percentage of pH3 positive cells and PCNA expression of intestinal mucosa, and EGCG could significantly increase percentage of pH3 positive cells and PCNA expression of intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…PCNA is a protein required for DNA synthesis and served as a marker of cell replication (Seifert et al. 2022 ). As showed in Figure 2a–d , I/R injury could reduce the percentage of pH3 positive cells and PCNA expression of intestinal mucosa, and EGCG could significantly increase percentage of pH3 positive cells and PCNA expression of intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is likely that increases in β cell mass and remodeling of β cell ultrastructure also contributed to the improvement in β cell function in the T2D-LCD and T2D-RYGB groups. Studies conducted in obese diabetic rats found that (a) weight loss increases β cell number and total β cell mass ( 29 ), and (b) even a small (11 mg/dL) chronic increase in plasma glucose concentration has adverse effects on the expression of islet cell genes associated with β cell viability and function ( 30 ), whereas decreasing plasma glucose with pharmacotherapy improves β cell ultrastructure and function, independently of weight loss ( 31 ). Although the results from our study appear to contradict previous studies that concluded that weight loss increases β cell function in people with obesity without T2D ( 8 , 18 , 20 , 32 , 33 ), β cell function in those studies was evaluated by using the disposition index or other indices that assessed insulin secretion/insulin concentration in relation to insulin sensitivity ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%